Philippines Financial Sector Assessment Program : Capital Markets Development - Moini, Yavar (World Bank, Washington, DC, 2021)
The Philippines corporate debt and equity markets will need to grow to provide alternative financing sources to support the strongly growing economy and emphasis on infrastructure spend. Capital markets deepening will be an essential pre-requisite for the country’s continued economic development. Well-functioning capital markets ensure the optimal allocation and pricing of capital. This enables retail and wholesale pools of capital to be efficiently deployed in a manner that maximizes returns for such owners of capital against their risk profile. Furthermore, there are a number of technical and operational issues that can be addressed, that can significantly improve the enabling environment for and functioning of the capital markets. The result of these factors has been a lack of focus in policy development and implementation that has hampered capital market development. Key issues include: a lack of commitment to reform from key stakeholders that has impeded the development of markets and market infrastructure; an onerous tax environment that has deterred issuance and investment; a continuing need to improve investor confidence by strengthening the quality of supervision and enforcement for market intermediaries and market operators; cumbersome regulatory requirements and processes around issuance, particularly debt issuance; and outdated and inefficient trading and post-trading infrastructure, and governance concerns regarding market operators. In order to effect meaningful change, a capital markets champion is required. This champion should be cognizant of the relevance of capital markets to the country and possess the will and vision to drive legislative, regulatory, and tax reforms. In addition, a commitment to initiate a change in the ownership and governance of key exchanges and enforce policy against entrenched interests will provide considerable impetus for development.